Assurance of learning: The impact of business core course reviews on students' scores on the comprehensive business exam for both internal and external comparative purposes. Issue 1 (2nd January 2019) - Hahn, William
Abstract: This study is the first to explore how business core course review sessions impact standardized test results. A statistically significant improvement in students' overall scores of 16.5% was identified when core course reviews were conducted between Comprehensive Business Exam pre- and posttest dates. As a result, institutional results moved from slightly above average to the upper 15th percentile among institutions employing this exam. Additionally, scores for the economics, finance, management, and marketing core-course subject matter areas significantly improved. A review did not significantly improve scores in the accounting concept area. Implications for assurance of learning analysis are presented.